Experimental study of natural convection heat transfer from a nonuniformly heated flat plate simulating PV panel - Wu, Shuang-Ying; Wu, Ying-Ying; Xiao, Lan; Yang, Zhen (Journal of mechanical science and technology, 2018)
In view of the characteristic of Photovoltaic (PV) conversion, an experimental study has been conducted to investigate the natural convection heat transfer from a flat plate. In order to simulate the real PV cells, three electrical heating circuits were employed to achieve a linear nonuniform heat flux boundary condition. The major parameters, such as the gradient parameter of heat flux k , tilt angle θ and heat flux q w were introduced to analyze their influence on heat transfer ability. Both the local temperature distribution and the overall trend of Nusselt number have been presented. Comparing with the uniform thermal boundary condition, the results show that the local convection heat transfer coefficient is fluctuated at the positions where heat flux has changed. When gradient parameter of heat flux increases, the difference of local convection heat transfer coefficient at the top of the plate between tilt angle θ = 0° and 90° becomes smaller. Moreover, it is observed that the gradient parameter of heat flux has a promotion effect on average convection Nusselt number at larger tilt angle, but the effect becomes complex as tilt angle is smaller. Finally, a correlation combining all significant factors has been put forward to estimate the natural convection heat transfer.